Quercetin modulates OTA-induced oxidative stress and redox signalling in HepG2 cells — up regulation of Nrf2 expression and down regulation of NF-κB and COX-2 - Ramyaa, Periasamy; krishnaswamy, Rajashree; Padma, Viswanadha Vijaya (Biochimica et biophysica acta, 2014)
Ochratoxin A (OTA), a mycotoxin, causes extensive cell damage, affecting liver and kidney cells. OTA toxicity is fairly well characterized where oxidative stress is believed to play a role, however, the sequence of molecular events after OTA-exposure, have not been characterized in literature. Further, antidotes for alleviating the toxicity are sparsely reported. The aim of this study was to understand the sequence of some molecular mechanisms for OTA-induced toxicity and the cytoprotective effect of quercetin on OTA-induced toxicity. Time course studies to evaluate the time of intracellular calcium release and ROS induction were carried out. The time of activation and induction of two key redox- sensitive transcription factors, NF-κB and Nrf-2 were determined by nuclear localization and expression respectively. The time of expression of inflammatory marker COX-2 was determined. Oxidative DNA damage by comet assay and micronucleus formation was studied. The ameliorative effect of quercetin on OTA-induced toxicity was also determined on all the above-mentioned parameters. OTA-induced calcium release, ROS generation and activated NF-κB nuclear translocation and expression. Pre-treatment with quercetin ameliorated ROS and calcium release as well as NF-κB induction and expression. Quercetin induced Nrf-2 nuclear translocation and expression. Quercetin's anti-inflammatory property was exhibited as it down regulated COX-2. Anti-genotoxic effect of quercetin was evident in prevention of DNA damage and micronucleus formation. Quercetin modulated OTA-induced oxidative stress and redox-signaling in HepG2 cells. The results of the study demonstrate for the first time that quercetin prevents OTA-induced toxicity in HepG2 cells. •Quercetin protects HepG2 cells from OTA-induced toxicity and inflammatory response.•OTA-induced toxicity was mediated by increased oxidative stress.•Quercetin modulated OTA-induced oxidative stress and redox-signalling.